Verification of Seasonal Fluctuation Effects of Fruits in the Inverse Demand System: The Evidence from Taiwan - Huang, Sheng-Ju; Lee, Jia-Jan (Asian Journal of Economic Modelling, 2018)
This study is focused on establishing the inverse demand system estimation model of Taiwanese fruits taking into account seasonal fluctuation effects. The settings of the model will be adjusted according to the verification obtained from documentary evidence. The seasonal fluctuation effects lead to an inverse demand function and inverse demand system restrictions. Taiwanese fruits are divided into five categories, such as bananas, pineapples, citrus, melons, and others. The data of volumes and prices were obtained from The Statistics of Food Supply & Utilization in Taiwan from 2006 to 2016. The results show that the scale flexibility and uncompensated own-price flexibility of each fruit category was negative, which were consistent with the theoretical requirement. The signs of uncompensated cross-price flexibility were mixed, which revealed that there existed complementary and substitute relationships between different categories of fruit. The seasonal fluctuation effects of fruits existed in the inverse demand system.